Pulmonary involvement and allergic disorders in inflammatory bowel disease - Tzanakis, Nikolaos E (The WJG Press and Baishideng, 2010)
Inflammatory bowel disease (IBD) has been associated with either clinical or subclinical airway and parenchymal lung involvement and interstitial lung complications. Several studies have reported that atopy has a high prevalence in IBD patients. Overlapping allergic disorders seem to be present in both the respiratory and gastrointestinal systems. The purpose of this review is to update clinicians on recent available literature and to discuss the need for a highly suspicious approach by clinicians.